Injection Laryngoplasty 2014: Indications, Techniques, and Pitfalls in Modern Vocal Fold Augmentation. (2nd September 2014) - Bock, Jonathan M.; Klein, Adam M.; Francis, David O.; Rubin, Adam D.; McWhorter, Andrew J.
Abstract : Program Description: Injection laryngoplasty has a long history in vocal fold augmentation, and its use continues to evolve in otolaryngology. This miniseminar will provide a contemporary update on the indications, injectable materials, operative techniques, and potential pitfalls of injection laryngoplasty in modern otolaryngology practice. Particular attention will be paid to the latest developments in injection materials and office‐based injection techniques for the general otolaryngologist. In addition, the presentation will include case presentations of pitfalls in injection laryngoplasty with a candid discussion of the inherent risks and possible mistakes that can be made with this technique and how to avoid them. Educational Objectives: (1) Define the various indications for injection laryngoplasty in modern otolaryngology practice and recognize the benefits and controversies of currently available injection materials for laryngoplasty. (2) Compare the benefits and indications for clinic or office‐based injection techniques, including thorough descriptions of clinic‐based injection techniques. (3) Recognize potential patient care risks with injection laryngoplasty and methods to avoid or ameliorate these risks.